The Effect of Centrifugation Time on the Quality of Domestic Chicken Spermatozoa Maintained at 5°C - Laura, Yosephine (2014)
The objective of this study was to determine the effect of centrifugation time on the quality of sperm diluted in diluter containing physiological sodium chloride and 20% yolk maintained in 5°C. Sperm was collected from 5 Pelung cocks aged of one year old. The quality of fresh semen was checked. Sperm was centrifugated as well as control (P0), centrifugated 15 (P1), 20 (P2), and 25 (P3) minutes. All sperm treatments were diluted (physiological sodium chloride added by 20% egg yolk) and maintained at 5° C. The quality of sperm such as pH, motility, viability, and abnormality were checked on storage after 0, 3, 6, 9, 12 and 24 hours. All of control and treatments combination were replicated for five replications. The data were analyzed using split-plot design with SPSS 17 for windows. The results showed that time of centrifugation had no effect on sperm quality but the time of storage had a significant-effect (P<0.01) on sperm quality. Time of centrifugation was significantly different (P<0.05) at 3 hours storaged motility. The averages of pH in each treatment (P0, P1, P2, and P3) were 6.31±0.33; 6.20±0.35; 6.18±0.35; and 6.20±0.35, respectively. The averages of motility in each treatment were 60±14.7%; 65.8±17.1%; 65±20.7%; and 67.2±19.7%, respectively. The averages of viability in each treatment were 54.5±22.3%; 64.1±21.6%; 58.6±22.8%; and 57.4±21.0%, respectively. The averages of abnormality in each treatment were 32.9±18.4%; 36.3±17.6%; 37.4±19.1%; and 36.4±15.3%, respectively. Motility in each treatment (P0, P1, P2, and P3) 3 hours storaged were 69.00±8.94%; 79.00±6.51%; 78.00±4.47%; and 82.00±5.70%, respectively. It can be concluded that centrifugation unable to maintain the sperm quality. The sperm quality decreased gradually during storage.